Management of human resources and productivity - Jain, Harish C. (Journal of business ethics, 1983)
A model for effective management of human resources for organizational effectiveness is proposed. Several elements of this model are evaluated in the light of the failure of personnel and industrial relations policies of organizations in Canada. Suggestions are put forward to improve worker performance and job satisfaction as well as organizational growth and survival.